2019
DOI: 10.1186/s13550-018-0471-8
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1, first-in-human study of 18F-GP1 positron emission tomography for imaging acute arterial thrombosis

Abstract: Background18F-GP1 is a novel positron emission tomography (PET) tracer that targets glycoprotein IIb/IIIa receptors on activated platelets. The study objective was to explore the feasibility of directly imaging acute arterial thrombosis (AAT) with 18F-GP1 PET/computed tomography (PET/CT) and to quantitatively assess 18F-GP1 uptake. Safety, biodistribution, pharmacokinetics and metabolism were also evaluated.MethodsAdult patients who had signs or symptoms of AAT or had recently undergone arterial intervention o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…99m Tc-apcitide was also shown to be ineffectual for diagnosis of PE ( 5 ). More recently, a PET probe targeting the GP2B3A receptor has been used to successfully image acute arterial and venous thrombi ( 4, 6 ). However, the specificity of this agent remains unknown, and the targeting of activated platelets, through the GP2B3A receptor, supports the detection only of active, hyperacute platelet-rich thrombi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…99m Tc-apcitide was also shown to be ineffectual for diagnosis of PE ( 5 ). More recently, a PET probe targeting the GP2B3A receptor has been used to successfully image acute arterial and venous thrombi ( 4, 6 ). However, the specificity of this agent remains unknown, and the targeting of activated platelets, through the GP2B3A receptor, supports the detection only of active, hyperacute platelet-rich thrombi.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of thrombosis this would include thrombus age, platelet content, fibrin content, risk of embolism and potential for lysis. A number of molecular imaging approaches incorporating different imaging modalities and targeting platelets ( 410 ), fibrin ( 1116 ), d-dimers ( 1720 ), or fibrinogen ( 21 ), have been proposed over the years, with some progressing to clinical trials ( 3, 22 ). However these agents have been limited by suboptimal pharmacokinetics, high blood background, low specificity, or sensitivity only to hyperacute/acute thrombi( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peter and colleagues have generated single-chain antibodies (scFv) with specific targeting toward the activated GPIIb/IIIa integrin, and no binding to resting platelets in circulation (150). This scFv have been conjugated to microbubbles for ultrasound (151), iron oxides particles or perfluorocarbon nanoemulsions for MRI (131), radiotracers for PET (137) and near-infrared dyes for optical imaging (137) of arteria and venous thrombi. Using this scFv, Yap et al successfully visualized a board range of tumors via ultrasound, PET and optical imaging (133).…”
Section: Potential Pathways For Platelet Involvement In Msmentioning
confidence: 99%
“…Clinical work has highlighted the development of the PET tracer 18 F-GP1, which is a novel tracer with a high affinity for GPIIb/IIIa on platelet surfaces (102). Following 18 F-GP1 injection, PET/CT researchers were able to monitor this tracer in a dynamic and systemwide manner, while analyzing plasma samples to assess 18 F-GP1 clearance and metabolism (103). They found that 18 F-GP1 exhibited satisfactory biodistribution and pharmacokinetic properties that made it ideal for the detection of atherosclerotic thrombosis.…”
Section: Radionuclide Imaging Of Thrombosismentioning
confidence: 99%